(untitled) (INNOVATIVE ECONOMY, 2022)
Kryvokulska N.M., Onofriichuk D.M. INNOVATIVE APPROACHES IN THE FUNCTIONAL ACTIVITY OF PUBLIC INSTITUTIONS TO ENSURE THE ECOLOGICAL DEVELOPMENT OF TERRITORIES Purpose. The aim of the article is to substantiate the importance of the implementation of functional activities to ensure the ecological development of territories and the use of innovative approaches in this activity. To achieve the goal, the following tasks were set: to substantiate that ecological development is a modern challenge; to prove the influence of globalization processes on the greening of the public sphere and the functional activity of public institutions in ensuring the ecological development of territories; to argue the significance of the greening of the economy and territorial ecological development at different levels and to determine the role and functional load of public institutions in this regard; to identify areas of use of innovative approaches in the functional activity of public institutions to ensure the ecological development of territories. Methodology of research. The following research methods were used to achieve the goal: system analysis, generalization – to characterize the functional load of public institutions in ensuring the ecological development of territories; institutional analysis – to determine directions for innovation of the functional activity of public institutions in ensuring the ecological development of territories. Findings. It was established that the factors produced as a result of the dynamism of the external environment affect all spheres of society’s life, forming modern challenges of a different nature and requiring innovative approaches in the functional activity of public institutions to ensure the ecological development of territories. It has been proven that “challenges” affect various processes (globalization, environmentalization, etc.). It is substantiated that there are problems in Ukraine at the national, regional and local levels, which are classified as global problems of our time and which relate to: interaction in the “nature-society” system; ensuring environmental security of development; taking into account the ecological component in social and economic, organizational and economic relations, as well as that these problems are directly related to the processes of functioning and development of the economy. It has been proven that the existence of a set of global environmental problems of today actualizes the issue of: deep integration of the environmental component into the national economy, that is, it is about greening the economy at the national, regional and local levels; application of innovative approaches in the functional activity of public institutions to ensure ecological development of territories. It is argued that the question of the need to innovate the functional activities of: educational institutions (state institutes) in the context of increasing their environmental load arises additionally; family (institute of family and upbringing) in terms of filling it with ecological content; religious organizations (social and cultural institute, institute of civil society) regarding the promotion of the ecological component of the life of the local population, the development of the spirituality of society. Originality. The advantages and value of ecologization of the economy, which by its content requires innovation of the functional load of all participants in ensuring the ecological development of the territory, in particular, public institutions, are determined. It is substantiated that the function of the state should be to stimulate the business entity to green its production activities through a change in the technological process of production, which in the long run will allow both the enterprise and the territory where such an enterprise operates to receive benefits. Practical value. The authors’ proposals can be used as a guideline for the implementation of the idea of practical use of innovative approaches in the functional activities of public institutions to ensure the ecological development of territories. Key words: public sphere, public institutions, social challenges, globalization, environmentalization, functional load of public institutions in ensuring ecological development of territories.